Electrophoretic techniques for purification, separation and detection of Kayvirus with subsequent control by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and microbiological methods - Marie, Horká; Dana, Štveráková; Jiří, Šalplachta; Karel, Šlais; Marta, Šiborová; Filip, Růžička; Roman, Pantůček (Journal of chromatography. A, 2018)
The bacteriophage K1/420 is a member of genus Kayvirus that was extensively studied as an alternative treatment to combat bacterial infections caused by antibiotic-resistant Staphylococcus aureus strains. Despite the promise of phage therapy, the development of clinical applications of phages is facing regulatory and technical hurdles before it can receive acceptance in the Western World. Suitable simple and accurate diagnostic techniques to control the quality of the phage, which would satisfy the requirements of regulatory authorities are still being discussed. Here, we present the conditions for the simultaneous separation and detection of phage K1/420 and S. aureus by CZE and by CIEF were found, and the phage isoelectric point was determined to be 3.6. After removing the cell debris, the phage was successfully purified from the crude phage lysate and pre-concentrated by preparative isoelectric focusing. Its zone was localized by the positions of colored pI markers in the cellulose bed. The phage from the harvested zone had a decreased ability to infect its host. However, it was suitable for its separation, detection and identification by capillary electrophoretic methods, MALDI-TOF MS and electron microscopy.
Keywords: Isoelectric Focusing; Staphylococcus Phages; stafylokokové bakteriofágy; Capillary electrophoretic methods; MALDI-TOF MS; Preparative IEF; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Pre-concentration; Humans; Separation; isoelektrická fokusace; Purification; Kayvirus; Staphylococcus aureus; lidé